POSSIBLE OCCURRENCE OF TOXIC AND HARMFUL PHYTOPLANKTON IN LOMBOK BAY, LOMBOK, INDONESIA - Sidharta, Boy Rahardjo; Ahyadi, Hilman (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2007)
Harmful Algal Bloom (HAB) incidences in Indonesian waters were increasingly occurred from time to time. Extensive and continous studies in this field are needed to be done in more areas in the country. This objective of this present survey were to determine the occurrence of potential toxic and harmful marine microalgae in Lombok, to reveal the diversity of marine microalgae found in the area, and to give some information on the occurrence of HAB phytoplankton in Lombok island. Plankton samples were taken from six stations in Lembar bay, Lombok on February, 2007. This survey found 23 marine microalgae species and two of those were potentially harmful and toxic, namely Dinophysis caudata and Gymnodinium catenatum. Four species, such as Ceratium spp, Dinophysis miles, Prorocentrum gracile, and P micans, were noted to be harmful though so far no report on adverse effect caused by these microalgae in the area. Diatom Chaetoceros spp were the most abundant phytoplankton in almost all of the sampling areas and followed by Ceratium furca and Protoperidinium sp.